PERPENDICULAR MAGNETIC ANISOTROPY AND ITS ELECTRIC FIELD MANIPULATION IN MAGNETIC MULTILAYERED HETEROSTRUCTURES - ONE, Roxana-Alina; MICAN, Sever; TIUSAN, Coriolan Viorel (Studia Universitatis Babeș-Bolyai Physica, 2021)
Understanding of underlying physics related to the Perpendicular Magnetic Anisotropy (PMA) in magnetic heterostructures represents a major issue for its exploit in random-access memory (MRAM) devices. Using ab-initio analysis, we reveal some basic aspects related to the anatomy of PMA and its variation with electric field in various X/Fe/MgO(001) multilayer configurations (X=Cr, Au, V, Ag, Pt, Pd,…) compatible with standard experimental architectures of magnetic tunnel junction devices. Our study quantifies and underlines the significant role of the Rashba interfacial field on PMA. We explain and correlate the sign, the magnitude, and the electric field dependence of the PMA, the Rashba coefficient αR and the Dzyaloshinskii–Moriya (DMI) asymmetric exchange interaction parameter. Moreover, when varying the Fe thickness in X/Fe/MgO(001) systems, we observe oscillations of PMA with the number of Fe monolayers, explained within the framework of quantum wells of the Δ1 Bloch symmetry electrons in Fe. Further atomistic micromagnetic simulations including different Fe layer thicknesses and the corresponding PMA predict macroscopic magnetization characteristics in realistic experimental systems.